Cellular and Molecular Pathology of Age-Related Macular Degeneration: Potential Role for Proteoglycans - Othman Al Gwairi; Lyna Thach; Wenhua Zheng; Narin Osman; Peter J. Little (Journal of Ophthalmology)
Age-related macular degeneration (AMD) is a retinal disease evident after the age of 50 that damages the macula in the centre of retina. It leads to a loss of central vision with retained peripheral vision but eventual blindness occurs in many cases. The initiation site of AMD development is Bruch’s membrane (BM) where multiple changes occur including the deposition of plasma derived lipids, accumulation of extracellular debris, changes in cell morphology, and viability and the formation of drusen. AMD manifests as early and late stage; the latter involves cell proliferation and neovascularization in wet AMD. Current therapies target the later hyperproliferative and invasive wet stage whilst none target early developmental stages of AMD. In the lipid deposition disease atherosclerosis modified proteoglycans bind and retain apolipoproteins in the artery wall. Chemically modified trapped lipids are immunogenic and can initiate a chronic inflammatory process manifesting as atherosclerotic plaques and subsequent artery blockages, heart attacks, or strokes. As plasma derived lipoprotein deposits are found in BM in early AMD, it is possible that they arise by a similar process within the macula. In this review we consider aspects of the pathological processes underlying AMD with a focus on the potential role of modifications to secreted proteoglycans being a cause and therefore a target for the treatment of early AMD.